2015
DOI: 10.1007/s00464-015-4141-x
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid NOTES transvaginal intraperitoneal onlay mesh in abdominal wall hernias: an alternative to traditional laparoscopic procedures

Abstract: Although no final conclusion can be made regarding the presumed non-inferiority of this technique in terms of recurrence and mesh infection compared with traditional laparoscopic IPOM, laparoscopic-assisted transvaginal IPOM is a feasible alternative to treat abdominal wall hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Although there is no clear consensus on the technique for ultimate surgical outcomes, the outcome of the umbilical hernia repair is evaluated by recurrence, postoperative chronic pain, and complications [15]. The recurrence rate is doubtlessly the most critical parameter in terms of the quality of the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no clear consensus on the technique for ultimate surgical outcomes, the outcome of the umbilical hernia repair is evaluated by recurrence, postoperative chronic pain, and complications [15]. The recurrence rate is doubtlessly the most critical parameter in terms of the quality of the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that the vaginal canal can be safer than the skin incision for abdominal imaging, peritoneal and liver biopsy, and insertion of a synthetic mesh 12,13 . The patient-related factors for the occurrence of trocar site hernias are advanced age, diabetes mellitus, and obesity 14 . Recurrent hernia repair, surgical site infection, and the extending the trocar site are also other surgical risk factors for the recurrence 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Safety and patient satisfaction were promising, and we further successfully implemented hybrid transvaginal techniques for appendectomies and intraperitoneal hernia repair. 20,21 The aim of our study was to assess outcome and complications of NOTES TVC, with a focus on evaluating necessity and consequences of pre- and postoperative routine gynecological examinations.…”
Section: Introductionmentioning
confidence: 99%